Análise da relação entre bem-estar e absenteísmo nos profissionais de enfermagem - Forcelini, Diogo Marmitt (2019)
The Burnout syndrome is an individual response to the chronic and prolonged stress in the work environment. This phenomenon happens frequently and intensely with nursing professionals around the world, due to its working characteristics that involve ethical, traumatic, violent and the terminality of human life issues. One of the possible consequences of this syndrome is the employee absenteeism. Characterized by the unexpected absence of workers in the exercise of their daily work activities, this phenomenon has become prevalent in the nursing category causing a shortage of skilled professionals, as well as economic damage to health care organizations. The present study has as an objective to evaluate the possible relationship observed between the Burnout syndrome in the nursing category and the absenteeism. This is a cross-sectional study with a quantitative approach, resulting from a survey using a probability sampling, which compares a census group of workers in absenteeism and another with the same number of workers not in absenteeism. The study has been conducted in the city of Passo Fundo, a health services hub in the state of Rio Grande do Sul. A survey form with sociodemographic data, questions from the Maslach Burnout Inventory (MBI) instrument and reduced scale of engagement has been used and applied to 201 nursing professionals, with 95 of them being in the condition of absenteeism and 106 who were not. The first scientific production of the study, “Absenteeism of nursing professionals and its impact on their well-being at work”, which aims to analyze the possible causality between the two conditions, has indicated that a high level of engagement for both groups of nursing professionals, in the absentee group as well as in the non-absentee. Both groups showed levels of engagement and it was not possible to identify differences between the results.